2002
DOI: 10.1046/j.1365-8711.2002.05280.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of negative superhumps in a low-mass X-ray binary an end to the long debate on the nature of V1405 Aql (X1916053)

Abstract: The detection of two similar periodicities (3001 and 3028 s) in the light curve of V1405 Aql, a low mass X‐ray binary (LMXRB), has attracted the attention of many observers. Two basic competing models have been offered for this system. According to the first, V1405 Aql is a triple system. The second model invokes the presence of an accretion disc that precesses in the apsidal plane, suggesting that the shorter period is the orbital period while the longer is a positive superhump. The debate on the nature of V1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 47 publications
2
71
0
Order By: Relevance
“…Finally, the source also showed a long-term 198.6 ± 1.72 d periodicity in X-rays (Priedhorsky & Terrell 1984), which has not been confirmed by further observations (see Retter et al 2002). To date the spin period of the neutron star in XB 1916-053 is not known.…”
Section: Introductionmentioning
confidence: 69%
“…Finally, the source also showed a long-term 198.6 ± 1.72 d periodicity in X-rays (Priedhorsky & Terrell 1984), which has not been confirmed by further observations (see Retter et al 2002). To date the spin period of the neutron star in XB 1916-053 is not known.…”
Section: Introductionmentioning
confidence: 69%
“…Patterson proposed that period deficits in negative superhumps are about half the period excesses in positive superhumps: − ≈ −0.5 + , where = (P superhump − P orbital )/P orbital . However, Retter et al (2002b) found a more precise relation in which the ratio φ = − / + was a function of orbital period. From their Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy has led to several interpretations including superhumps (Schmidtke 1988) and a hierarchical triple system Send offprint requests to: L. Boirin, e-mail: L.Boirin@sron.nl model (Grindlay et al 1988). Retter et al (2002) recently favored the superhump model, which invokes a precessing accretion disk, and which identifies the X-ray period as orbital. XB 1916-053 is a type I X-ray burster (Becker et al 1977), indicating that the compact object is a neutron star.…”
Section: Introductionmentioning
confidence: 99%